DOCUMENTING OUR TRAUMATIC PRACTICE - Collins, Anthony (PINS-Psychology in Society, 2025)
Kaminer, D & Eagle, G (2010) Traumatic stress in South Africa. Johannesburg: Wits University Press. ISBN 978-1-86814-509-6. Pages x + 222 It is symptomatic of the state of South African society that we have been a leader in the area of trauma support for several decades. During the 1980s various organisations emerged to provide support for victims of political and gender-based violence. The political changes of the 1990s substantially changed this situation, but while the repressive state violence of the Apartheid era came to an end, other patterns of victimization have continued. There is little evidence to suggest that violence against women and children has decreased, and there is continuing widespread anxiety about violent crime. In addition, the AIDS epidemic has increased experiences of anxiety and loss, and other patterns of violence such as nationwide xenophobic attacks have emerged. One consequence of this constant state of crisis is that despite the advanced state of interventions, trauma workers have had relatively little time to reflect on their experiences, which explains why it has taken so long to produce this first major book on traumatic stress in South Africa.